Pemuda Menghadapi Ketidakpastian dalam Pasar Tenaga Kerja: Analisis Ketahanan dan Ambivalensi dalam Perspektif Sosiologi - Deandra Rafiq Daffa; Dave Arthuro; M. Bintang Widya Pratama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The transformation of the modern labor market has posed significant challenges for young people, particularly in the form of career uncertainty, excessive work flexibility, and the mismatch between education and labor market demands. This study aims to explore how Indonesian youth respond to these conditions through the lens of ambivalence and resilience theories by Colombo & Rebughini. The research uses a qualitative method with in-depth interviews involving two university graduates working in fields unrelated to their academic backgrounds. The findings reveal that the lack of job stability, economic pressure, and educational mismatch drive young people to develop various adaptive strategies. These include personal resilience such as introspection and optimism, as well as social resilience supported by family and peer networks. Furthermore, the meaning of work among youth is shifting—not merely as a source of income, but as a space for self-actualization, skill relevance, and psychological comfort. This is consistent with previous studies in SINTA-indexed journals, which emphasize that Indonesian youth today are redefining success and meaningful work within an increasingly ambivalent social landscape. The study concludes that youth are not merely passive victims of economic uncertainty but are also active agents in constructing their own narratives of work and life. Therefore, it is essential for educational institutions, industries, and the state to provide adaptive environments that allow youth to grow sustainably within a dynamic labor ecosystem.